Age-morphology dependence of the Milky Way boxy/peanut bulge seen in Mira variables - Semczuk, Marcin; Dehnen, Walter; Schönrich, Ralph; Athanassoula, E (Monthly notices of the Royal Astronomical Society, 2022)
We analyse the distribution of Mira variable stars in the central region of the Milky Way. We find that with increasing period, i.e. decreasing age, the Miras shift towards negative Galactic longitudes ℓ. Comparing to a cosmological zoom simulation of a barred galaxy, we find that this shift with age can be explained by an age-morphology dependence of the boxy peanut/bulge. Owing to a combination of projection effects and the limitation of the range of Galactic longitudes, the near hump at ℓ > 0 is more truncated for younger populations, and the far hump at ℓ < 0 dominates the observed distributions.